Português língua estrangeira (PLE) para estrangeiros - Gileno, Rosangela Sanches da Silveira [UNESP]; Santana, Leonardo Arctico [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project, coordinated by Prof..Dra.Rosangela Sanches da Silveira Gileno and by Prof. Dra. Nildicéia Ap. Rocha, meets foreign undergraduates and postgraduate students of the 4 units of UNESP Araraquara: Faculty of Science and Letras (FCLAr), Faculty of Pharmacy (FF), Faculty of Odontology (FO), Institute of Chemistry (IQ); and external community. Cultural activities and Portuguese as a Foreign Language (PLE) courses are offered semi-annually in Basic, Intermediate and Advanced levels, focusing on cultural and intercultural aspects of the discursive and communicative diversity of Brazil.

O projeto, coordenado pela profa. Dra. Rosangela Sanches da Silveira Gileno e pela profa Dra. Nildicéia Ap. Rocha, atende alunos estrangeiros de graduação e pós-graduação das 4 unidades da UNESP de Araraquara: Faculdade de Ciências e Letras (FCLAr), Faculdade de Farmácia (FF), Faculdade de Odontologia (FO), Instituto de Química (IQ); e comunidade externa. Semestralmente são oferecidas atividades culturais e cursos de Português Língua Estrangeira (PLE) em níveis Básico, Intermediário e Avançado, com foco em aspectos culturais e interculturais da diversidade discursivo-comunicativa do Brasil.
Keywords: Portuguese foreign language; Education; Internationalization; Português língua estrangeira; Educação; Internacionalização